Cardiovascular and type 2 diabetes risk factors in Liberian nurses - Noble Donkor (International Journal of Africa Nursing Sciences, 2016)
Background: Type 2 diabetes and cardiovascular disorders are fast growing global health burdens especially in low and middle income countries. The aim of this study was to assess the risk factors of these diseases among male and female nurses in Liberia. Methods: The random sample of this cross-sectional study was collected from 95 Liberian nurses (63 females and 32 males) who had attended the International Nursing Education Conference in Monrovia. Data about body mass index (BMI), waist circumference (WC), systolic (SBP) and diastolic blood pressure (DBP) and fasting blood glucose (FBG) were collected. The relationships between the measured risk factors and fasting blood glucose were explored using regression analysis. Results: Over 29% of females and 31% of males had one or more of the measured cardiovascular and type 2 diabetes risk factors. Among females, 50% were overweight or obese or centrally obese, 20% had elevated SBP and DBP, and 70% had elevated FBG. Among males, 45% were overweight or obese or centrally obese, 20% had elevated SBP and DBP, and 66% had elevated FBG. BMI was positively related to WC among both females and males. WC was positively related to SBP and DBP and FBG among both females and males. BMI had a significant relationship with SBP and DBP and FBG among both females and males. Conclusion: These observations suggest that reducing the identified risk factors may be important for primary prevention and management of type 2 diabetes and cardiovascular disorders.